The intimate geographies of Anna Maria Maiolino. Issue 1 (2nd January 2022) - Sutherland, Camilla
Abstract : This article examines the intersection of identity and spatiality in the works of Brazilian visual artist Anna Maria Maiolino. It situates her within a broader discussion of artistic cartographies in Latin America and beyond, and charts Maiolino's recurrent engagement with the map as a symbol and mapping as a process. Analysing the artist's explorations of spatiality in political, psychological, and corporeal terms, this article proposes that Maiolino's work articulates an experience of nomadic subjectivity and a destabilisation of ideas of national and continental belonging.